Assessment of fetal cardiac diastolic function of gestational diabetes mellitus using dual-gate Doppler. Issue 28 (16th July 2021) - Hou, Qingsha; Yan, Fang; Dong, Xudong; Liu, Huanling; Wu, Jie; Li, Jiao; Ding, Yunchuan
Abstract : Abstract: Gestational Diabetes Mellitus (GDM), as a common complication of pregnancy, has an increasing trend globally. GDM leads to maternal complications and fetal complications. Fetal cardiac diastolic dysfunction is strongly associated with GDM. This study aims to assess the ventricular diastolic function of fetuses exposed to GDM by looking into the diagnostic parameters using both conventional method and Dual-gate Doppler method (DD). And to investigate the potential of DD method in early detection of fetal cardiac diastolic dysfunction. 56 women diagnosed with GDM and 55 non-GDM pregnant women were enrolled in their 24 to 30 weeks of gestation. Conventional method and DD method were applied to measure mitral and tricuspid inflow velocities E-waves, A-waves on pulsed-wave Doppler, and mitral and tricuspid annular velocities e′-waves, a'-waves on Tissue Doppler imaging. E/A, e'/a' and E/e′ ratio was calculated. The difference between GDM and control groups was statistically tested and analysed using one-sample Kolmogorov-Smirnov test, Student t test, Mann-Whitney U test and Kruskal-Wallis test and Bland–Altman plot analysis. Intraobserver intraclass correlation coefficients of E/A, e'/a', and E/e' value of both mitral and tricuspid valve are all greater than 0.80, while interobserver intraclass correlation coefficients are between 0.71 and 0.88. Right (6.35 vs 6.79; P = .001) ventricular function showed significantly lower E/e' ratios in the GDM group compared with control fetuses by conventional method. Both left (6.16 vs 6.59; P = .036) and right (6.28 vs 6.75; P = .01) ventricular function showed significantly lower E/e' ratios in the GDM group compared with control fetuses by DD method. Exposure to high level of maternal blood glucose leads to impaired diastolic function in the fetuses. Fetal right ventricular function is a potential key point to study to enable an early detection for fetal diastolic dysfunction since the alteration and damage are more likely to happen in right ventricular. Measurement of E/e' ratio using DD method is considered as a promising method in fetal cardiac diastolic function assessment. Well or poorly control of the GDM does not have significant influence on the fetal diastolic function thus an early detection of GDM and GDM induced fetal cardiac dysfunction is necessary.